Ancient North America : - Fagan, Brian M. (Thames & Hudson, 2000)
Since its first edition in 1990, Ancient North America has been praised as a definitive synthesis of North American archaeology. The third edition continues the tradition in an extensive revision that includes new material on climate change and its effect on West Coast societies, additional coverage on the importance of ideology and power in Mississippian chiefdoms such as Cahokia and Moundville, and information on the latest discoveries in the Arctic and along the northwest coast.